Study on Determination of Polyphenols in Tobacco by Gas Chromatography-Mass Spectrometry - Shi, Hong-Lin; Xu, Yi-Ran; Miao, Ming-Ming; Yang, Guang-Yu; Hu, Qiu-Fen (Asian Journal of Chemistry, 2010)
A gas chromatography-mass spectrometry method for the determination of polyphenols (chlorogenic acid, rutin and scopoletin) in tobacco samples was studied. The polyphenols were extracted from the samples by ultra-sonic extraction and a 99:1 mixture of N,O bis(trimethylsilyl)- trifluoroacetamide and trimethylchlorosilane was used for derivatization. With GC-MS detection in single-ion-monitoring mode, the main polyphenols (chlorogenic acid, rutin and scopoletin) were analyzed quantitatively. The limit of detections (S/N = 3) were below 50 ng/mL, the relative standard deviations (RSD) were below 3.2 % (n = 7) and the recoveries were in the range of 92-106 %.